Elucidating the Elephant: Interdisciplinary Law School Classes - Kim Diana Connolly (Washington University Journal of Law & Policy, 2003)
This Essay explores the use of interdisciplinary law school classes as a fundamental way to connect law students with future colleagues who are receiving different professional training, as well as with concepts related to but outside of traditional doctrinal law. While these classes offer rich learning opportunities, their design and implementation present a host of different issues. Part I of this Essay briefly explores the history and range of interdisciplinary class opportunities, looking both outside and within the law school context. Part II provides an overview of the benefits and barriers to successful interdisciplinary law school courses. Part III offers some ideas about effective interdisciplinary class design. Part IV provides a brief case study of the issues discussed in the previous parts by examining the interdisciplinary course that I teach, the Environmental Advocacy Seminar. The Essay concludes that interdisciplinary courses are important insofar as they help students elucidate the “elephants” they will encounter in law practice. Moreover, it concludes that interdisciplinary study may well hold the key to truly understanding the nature of our entire profession, which, like the fabled blind men, we tend to experience from our own limited perspectives.
Keywords: Law schools -- Curricula; Interdisciplinary approach in education; Interdisciplinary approach (Education); Law schools; Legal education; United States